Kissing atypical melanocytic nevus of genital type of the labia majora in a young Bulgarian patient. What’s the best approach? (Dermatology Reports, 2023)
Melanocytic lesions, especially in delicate anatomical locations such as the vulva, penis, mons pubis etc, are challenging to diagnose. The patients may delay physical examinations due to anxiety or discomfort from the location of the lesion. In terms of therapy options, the surgical approach is not always the preferred one, but it is the one that could lead to a definitive solution to the problem. A limited number of studies do not exclude that atypical nevi of genital type could be considered as melanoma precursors. Single case reports have identified atypical genital nevi of the labia majora as a risk factor for genital melanoma development. Lesions that occupy a larger area than the labia majora and extend into the areas around them are particularly problematic, because the result of a single biopsy could be misleading. Therefore, careful physical examinations are mandatory. Mechanical irritation in the genital area, and in particular in the labia majora region, is an additional reason for choosing the surgical-reconstructive therapeutic option. We present a 13-year-old female with a progressive kissing divided nevus, located in the area of the vulva and labia majora, extending to the mucosa. A biopsy was taken in order to rule out malignancy. Immunohistochemistry was performed with specific melanocyte markers S-100, HMB-45 and SOX confirming the benign origin of the lesion. A diagnosis of atypical melanocytic nevus of genital type was made. For prevention a surgical excision was advised but later on declined by the patient’s parents. Further close observation of the lesion was recommended.